PENGARUH WORKPLACE BULLYING DAN ABUSIVE SUPERVISION TERHADAP CYBERLOAFING MELALUI EMOTIONAL EXHAUSTION KARYAWAN MILLENIAL E-COMMERCE JAKARTA SELATAN - Aulia Rahma; Netania Emilisa; Indrayani Nur Aini; Cika Cika; Aicha Fatiha Jolie (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study analyzes the influence of workplace bullying and abusive supervision on cyberloafing mediated by emotional exhaustion in millennial generation employees working in e-commerce in South Jakarta. The data used are primary data, and using purposive sampling with online distribution to 165 respondents. The hypothesis testing technique uses Structural Equation Modeling and previously tested the instrument using validity and reliability. The findings indicate that workplace bullying and harsh supervision have a positive effect on emotional exhaustion, while emotional exhaustion has an effect on cyberloafing, while workplace bullying and harsh supervision mediated by emotional exhaustion have a positive effect on cyberloafing. This study is limited to e-commerce companies in South Jakarta millennial generation; therefore, future research to expand the sector, generation and include additional variables to improve understanding.